Advances in production management systems. production management for data-driven, intelligent, collaborative, and sustainable manufacturing : IFIP WG 5.7 International Conference, APMS 2018, Seoul, Korea, August 26-30, 2018, Proceedings /: production management for data-driven, intelligent, collaborative, and sustainable manufacturing : IFIP WG 5.7 International Conference, APMS 2018, Seoul, Korea, August 26-30, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available